A new synonym with a new species of Rhopalopsole (Plecoptera: Leuctridae) from China - Yang, Yu-Ben; Du, Yu-Zhou (Zootaxa, 2021)
Recently, we reviewed the specimens of the genus Rhopalopsole Klapálek, 1912 we have collected and checked the holotype and paratypes of Rhopalopsole duyuzhoui Sivec & Harper, 2008. We present morphological evidence that R. duyuzhoui is a junior synonym of Rhopalopsole basinigra Yang & Yang, 1995, and that R. basiningra is a new distribution record to Guizhou Province, southwestern China. Additionally, a new species of this genus from Guizhou Province, Rhopalopsole dicondylica Yang & Du, sp. nov. is described and illustrated. The new species is compared to the similar species of this genus.